Biomonitoring mercury pollution in Juru industrial estate using a rapid inhibitive enzyme assay - Uba, Garba; Halmi, Mohd Izuan Effendi; Shukor, Mohd Yunus (Hibiscus Publisher, 2024)
Due to rapid industrialization coupled with indiscriminate release of pollutants, the number of polluted rivers in Malaysia has been steadily increasing over the years. Regular monitoring of contaminants, particularly heavy metals, is not feasible due to the steep cost of instrumental monitoring alone. In this study, a rapid inhibitive enzyme assay using the molybdenum-reducing enzyme from the bacterial isolate 34XW was developed for monitoring mercury. The Mo-reducing enzyme from this bacterium was very sensitive to mercury, with an IC₅₀ confidence interval of 0.0025–0.0029. The inhibition model followed a log(inhibitor) vs. response with variable slope, enabling detection of mercury at the Maximum Permissible Limit (MPL) set by the Malaysian Department of Environment. Comparisons with established assays, using IC₅₀ values and confidence intervals, confirmed the superior sensitivity of the developed method. Hierarchical clustering identified patterns of enzyme sensitivity, with assays grouped by IC₅₀ intervals. Isolate 34XW was an outlier with exceptional sensitivity. K-Means clustering grouped assays into sensitivity tiers, with the clustering of the molybdenum-reducing enzyme from the bacterial isolate 34XW into a unique cluster due to the level of its sensitivity. Juru industrial estate water samples tested using the assay revealed its capability in detecting low concentrations of mercury. These findings underscore the assay’s utility in detecting elevated mercury concentrations in environmental samples and its broader implications for environmental monitoring and biochemical applications. As a preliminary screening tool for heavy metal monitoring on a large scale, the assay is quick and easy to use.